Looking ahead with a look behind - Call, Edward P. (Kansas Agricultural Experiment Station, 2011)
The current economic situation dictates that dairy producers use all available tools and resources to maximize efficiency. Yearly milk yield is the most reliable predictor of profitability. Because the genetic base dictates each cow’s potential for converting feed into milk, using 80+ percentile proved sires is strongly recommended along with a 100% commitment to artificial insemination of cows and heifers. Current technology allows dairy producers to make significant gains in resolving poor reproductive performance. A user friendly recordkeeping system to routinely measure individual cows’ productivity along with overall herd performance is essential for maximizing return on capital investment.
Keywords: Dairy; Yearly milk yield